Enhancement of reproducibility and reliability in a high-performance flexible thermoelectric generator using screen-printed materials. (April 2018) - Choi, Hyeongdo; Kim, Yong Jun; Kim, Choong Sun; Yang, Hyeong Man; Oh, Min-Wook; Cho, Byung Jin
Abstract: Flexible thermoelectric generators (f-TEGs) have recently attracted significant attention because they can be applied to non-flat surfaces and used as semi-permanent power sources. The use of screen printing to fabricate f-TEGs would enable large-scale, mass production. To realize this aim, several hundred pairs of thermoelectric (TE) materials formed by screen printing must all exhibit uniform TE properties. However, parameter deviation commonly occurs in such batches because the materials formed by screen printing are usually crystallized in a large furnace or chamber. We report here a new crystallization process that avoids these problems while improving the output characteristics of the f-TEGs, using screen printed thermoelectric elements (sp-TEs). The sp-TEs were formed with a paste containing an excess of tellurium, which allowed a single-step crystallization process to be developed. The simplified process improved the low density associated with conventional sp-TE fabrication (to 6.23 g cm −3 for Bi.5 Sb1.5 Te3 and 6.43 g cm −3 for Bi2 Te2.7 Se.3 ), and reduced the deviation in TE parameters (Seebeck coefficient, electrical and thermal conductivity) to less than half of the conventional range. As a result, the highest material figure of merit (ZTMAT ) values among sp-TEs was achieved for both p-type sp-TE (0.93 ± 0.020) and n-type (0.64 ± 0.025) at room temperature. F-TEGs consisting of 200 couples of the improved sp-TEs produced an output power density of 5.23 ± 0.2 mW/cm 2 at a temperature difference (ΔT) of 25 K, demonstrating the feasibility of mass producing high-output f-TEGs with reliability and reproducibility. Graphical abstract: fx1 Highlights: A new crystallization process for screen-printed TE materials (sp-TEs) is proposed. The reproducibility of f-TEG is greatly improved by reducing the deviation of sp-TE. The average ZTM A T s of p- and n-type sp-TEs through mass production are 0.93 and 0.64. Fabricated f-TEGs achieve a high power density of 5.23 ± 0.2 mW/cm 2 with ΔT = 25 K.